Correction: Quad-rotor-shaped non-fullerene electron acceptor materials with potential to enhance the photoelectric performance of organic solar cells. Issue 30 (16th July 2019) - Yao, Chuang; Yang, Yezi; Li, Lei; Bo, Maolin; Peng, Cheng; Wang, Jinshan
Abstract : Correction for 'Quad-rotor-shaped non-fullerene electron acceptor materials with potential to enhance the photoelectric performance of organic solar cells' by Chuang Yao et al., J. Mater. Chem. A, 2019, DOI: ;10.1039/c9ta04084f .